!nnovation : how innovators think, act and change our world - McDonald, Kim Chandler (London ; Philadelphia : Kogan Page, 2013)
" Businesses looking to succeed in the digital, global economy must innovate to survive, and !nnovation highlights the pioneers who have broken the mold and led the pack in every field, from IT to food, fashion to healthcare. Innovation expert, Kim Chandler McDonald underlines the common denominators linking these highly creative people, such as their compulsion to tell their truth, unpalatable or not, their entrepreneurial instincts and their steadfast protection of their brands. This book offers: --understanding of innovation as a mindset rather than a process --insight on how to start thinking like an innovator and into how this can assist them with their own careers and goals --knowledge of how to cultivate innovation in their own team, department or business --personal accounts from international innovators !nnovation showcases interviews with over 100 people who have pushed aside the boundaries in their field, such as: Matt Flannery, CEO/Co-Founder of Kiva, the microfinancing organization working to alleviate poverty; author Seth Godin; Zappos CEO Tony Hsieh; Digital Royalty CEO Amy Jo Martin; and Chief Innovation Officer at the marketing agency MDC Partners, Faris Yakob. Chandler McDonald finds out what drives these successful innovators, what makes innovations take off and why innovation is so critical to individuals, economies and to society as a whole"--
Machine generated contents note: -- Acknowledgements -- About the AuthorThe orchestration of innovation01 The me-conomics of the GDE -- Innovating from the e-conomy to the me-conomy02 The state of the nation addressed -- Taking stock of how things stack up03 Flat world navigators connecting the dots04 me-health -- Resolute and committed stakeholders at the heart of the healthcare industry05 Innovating educating 06 The power of the me-dia -- Demanding what you want delivered when, where and how you want it07 Being grounded when the sky's the limitSummary -- Biographies.
Includes bibliographical references and index.
Description based on print version record.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Creative ability in business; Success in business; Technological innovations; Organizational change; Electronic books